Antibiotic prescribing for acute respiratory tract infections in Norwegian primary care out-of-hours service - Bent H. Lindberg; Svein Gjelstad; Mats Foshaug; Sigurd Høye (Taylor & Francis Group, 2017)
Purpose: To examine factors correlating with antibiotic prescribing for acute respiratory tract infections (ARTIs) in Norwegian primary care out-of-hours service. Materials and methods: Retrospective data analysis for the year 2014 in two out-of-hours primary care units located in the towns of Hamar and Tønsberg in Norway, analysing type and frequency of different antibiotics prescribed by 117 medical doctors for ARTIs, and factors correlating with these. Results: The 117 doctors in two out-of-hours units diagnosed 6757 cases of ARTIs. 2310 (34.2%) of these resulted in an antibiotic prescription, where of 1615 (69.9%) were penicillin V (PcV). Tonsillitis and sinusitis were the two ARTI diagnoses with the highest antibiotic prescription rate. The antibiotic prescription rate increased successively with increasing activity level, measured as shorter median duration of consultations per session, from 28.7% (reference) in the least busy quintile of sessions to 36.6% (OR: 1.38 (95% CI =1.06-1.80)) in the busiest quintile of sessions. Prescribing of broad-spectrum antibiotics was not correlated with median duration of consultations per session. Female doctors had an OR of 0.61 (0.40-0.92) of a broad-spectrum antibiotic prescription compared to their male colleagues. Conclusions: Antibiotic prescribing for ARTIs in the primary care out-of-hours services investigated is at the same level as in Norwegian general practice, but with a higher prescription rate of PcV. Antibiotic prescribing increases on busy sessions, measured as median duration of consultations per session. The work frame in primary care out-of-hours service might influence the quality of clinical decisions.